Corporate governance and firm performance: an empirical study in Vietnam - Tran, Huu Manh (2020)
This empirical study investigates the relationship between corporate governance and firm performance for listed companies in Viet Nam. In this study, the author characterized corporate governance by the Board of Director's size, CEO duality, Board of Directors independence, managerial ownership, state ownership, and audit quality. Also, firm performance is measured by accounting-based measurement (ROA and ROE). The study used STATA to analyze panel data of 144 companies during the period 2016–2019. The results indicated a negative relationship between Board independence and firm performance and the positive relationship between CEO duality and firm performance in the regression model of ROA. Besides, ownership of the Board of Manger is found to affect positively ROE